Quasiperiodic shrimp-shaped domains in intrinsically coupled oscillators - de Souza, Silvio L. T.; Batista, Antonio M.; Medrano-T, Rene O. [UNESP]; Caldas, Iberê L. (AIP Publishing, 2024)
We report remarkable pattern formation of quasiperiodic domains in the two-dimensional parameter space of an intrinsically coupled system, comprising a rotor and a Duffing oscillator. In our analysis, we characterize the system using Lyapunov exponents, identifying self-similar islands composed of intricate regions of chaotic, quasiperiodic, and periodic behaviors. These islands form structures with an accumulation arrangement, denominated here as metamorphic tongues. Inside the islands, we observe Arnold tongues corresponding to periodic solutions. In addition, we surprisingly identify quasiperiodic shrimp-shaped domains that have been typically observed for periodic solutions. Similar features to the periodic case, such as period-doubling and secondary-near shrimp with three times the period, are observed in quasiperiodic shrimp as torus-doubling and torus-tripling.